The Effectiveness of Group Guidance Services Using Cinema Therapy Techniques to Increase the Entrepreneurial Interest of SMK Ganesha Tama Boyolali Students - Erik Prakoso; Ratna Wahyu Widyaningsih; Usmani Haryanti (Yayasan Adra Karima Hubbi, 2024)
The effectiveness of group guidance services uses cinema therapy techniques to increase the entrepreneurial interest of students of SMK Ganesha Tama Boyolali. Article, Guidance and Counseling Study Program, Faculty of Teacher Training and Education, Tunas Pembangunan University of Surakarta. This research was motivated by the low interest in entrepreneurship of students of SMK Ganesha Tama Boyolali. The low interest in entrepreneurship is shown by the number of students who do not want to become entrepreneurs because many students are afraid to build their own business or business, they do not have the courage, are not confident in their abilities, many students think that when building their own business, they will fail and cannot guarantee their success later. Many students of SMK Ganesha Tama Boyolali prefer to become employees rather than having to build their own business. The purpose of this study is to determine the effectiveness of group guidance services using cinema therapy techniques to increase the entrepreneurial interest of students of SMK Ganesha Tama Boyolali. This study uses a quantitative method with a type of pre-experimental research design model one groub pretest-posttest design. The population in this study is 34 students in grade XI of SMK Ganesha Tama Boyolali. The sampling technique uses the purposive sampling technique, where the sampling in this study amounted to 8 students of class XI RPL SMK Ganesha Tama Boyolali. The data collection method uses questionnaires and documentation. The instrument validity test uses the product moment formula, reliability with the Cronbach alpha formula, and data analysis uses the paired sample t test. The results of data analysis with the paired sample t test, showed that (M = 86.63, SD = 11. 526) while the post test value after the treatment changed to (M = 97.38, SD = 12.397), t (7) = -8.700, sig. (2 Tailed) = 0.000 p < (0.05) means that there is a significant difference between the pre-test and post-test results. Based on the results of the test, it can be concluded that group guidance services using Cinema Therapy Techniques are effective in increasing the entrepreneurial interest of students of SMK Ganesha Tama Boyolali. Keywords: Group Guidance, Cinema Therapy Techniques, Entrepreneurial Interest